2015
DOI: 10.1126/scitranslmed.aaa3097
|View full text |Cite
|
Sign up to set email alerts
|

Producing nitric oxide by pulsed electrical discharge in air for portable inhalation therapy

Abstract: Inhalation of nitric oxide (NO) produces selective pulmonary vasodilation and is an effective therapy for treating pulmonary hypertension in adults and children. In the United States, the average cost of 5 days of inhaled NO for persistent pulmonary hypertension of the newborn is about $14,000. NO therapy involves gas cylinders and distribution, a complex delivery device, gas monitoring and calibration equipment, and a trained respiratory therapy staff. The objective of this study was to develop a lightweight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 36 publications
0
52
0
2
Order By: Relevance
“…We previously demonstrated that NO produced by an electric plasma generator caused pulmonary vasorelaxation in lambs with pulmonary vasoconstriction induced by infusing U46619, a thromboxane analog. Both the offline and inline plasma NO generators reliably reduced the lamb's pulmonary vascular resistance (PVR) and pulmonary artery pressure (PAP) (5).…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that NO produced by an electric plasma generator caused pulmonary vasorelaxation in lambs with pulmonary vasoconstriction induced by infusing U46619, a thromboxane analog. Both the offline and inline plasma NO generators reliably reduced the lamb's pulmonary vascular resistance (PVR) and pulmonary artery pressure (PAP) (5).…”
Section: To the Editormentioning
confidence: 99%
“…We recently developed a novel method of synthesizing NO from air or oxygen (O 2 )-rich gas mixtures by electric plasma generation (5). Two NO generators were built: an offline device, which continuously produces the gas and maintains a constant concentration of NO throughout the respiratory cycle, and an inline generator, which produces NO for 800 milliseconds beginning 20 milliseconds after the onset of inspiration.…”
Section: To the Editormentioning
confidence: 99%
“…However, these methods produce large amounts of toxic by products, such as nitrogen dioxide (NO 2 ) and ozone (O 3 ), requiring complex purification systems [12; 13]. Recently, we designed, developed, and tested in lambs a lightweight, economic, and portable NO generation system using pulsed electrical discharge [14]. The prototype NO generation system produced a therapeutic range of NO (5–80 parts per million (ppm)) in air or an oxygen-enriched nitrogen containing gas [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we designed, developed, and tested in lambs a lightweight, economic, and portable NO generation system using pulsed electrical discharge [14]. The prototype NO generation system produced a therapeutic range of NO (5–80 parts per million (ppm)) in air or an oxygen-enriched nitrogen containing gas [14]. Iridium or other noble metal electrodes produced the lowest fractional amount of NO 2 /NO compared to nickel, carbon or tungsten electrodes [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation